Association between magnesium in drinking water and atrial fibrillation incidence: a nationwide population-based cohort study, 2002-2015 - Kirstine Wodschow; Cristina M. Villanueva; Mogens Lytken Larsen; Gunnar Gislason; Jörg Schullehner; Birgitte Hansen; Annette Kjær Ersbøll (BMC, 2021)
Abstract Background Atrial fibrillation (AF) is a common heart rhythm disorder and a risk factor of adverse cardiovascular diseases. Established causes do not fully explain the risk of AF and unexplained risk factors might be related to the environment, e.g. magnesium in drinking water. Low magnesium levels in drinking water might be associated with higher risk of cardiovascular diseases including AF. With detailed individual data from nationwide registries and long-term magnesium exposure time series, we had a unique opportunity to investigate the association between magnesium in drinking water and AF. Objective We evaluated the association between magnesium concentration in drinking water and AF risk. Methods A nationwide register-based cohort study (2002-2015) was used including individuals aged ≥30 years. Addresses were linked with water supply areas (n = 2418) to obtain time-varying drinking water magnesium exposure at each address. Five exposure groups were defined based on a 5-year rolling time-weighted average magnesium concentration. AF incidence rate ratios (IRRs) between exposure groups were calculated using a Poisson regression of incidence rates, adjusted for sex, age, and socioeconomic position. Robustness of results was investigated with different exposure definitions. Results The study included 4,264,809 individuals (44,731,694 person-years) whereof 222,998 experienced an incident AF. Magnesium exposure ranged from 0.5 to 62.0 mg/L (mean = 13.9 mg/L). Estimated IRR (95% CI) compared to the referent exposure group (< 5 mg/L) was 0.98 (0.97-1.00) for the second lowest exposure group (5-10 mg/L), and 1.07 (1.05-1.08) for the two highest exposure groups (15-62 mg/L). Strongest positive associations were observed among those aged ≥80 years and with lowest education group. An inverse association was found among individuals with highest education group. Conclusion There might be a small beneficial effect on AF of an increase in magnesium level in drinking water up to 10 mg/L, though an overall positive association was observed. The unexpected positive association and different associations observed for subgroups suggest a potential influence of unaccounted factors, particularly in vulnerable populations. Future research on magnesium in drinking water and cardiovascular diseases needs to focus on contextual risk factors, especially those potentially correlating with magnesium in drinking water.